INOVASI GURU MADRASAH DINIYAH DALAM MENGATASI PROBLEMATIKA PEMBELAJARAN BACA TULIS AL-QUR’AN DI ERA COVID 19 - Wijartini, Vina (Rabbani: Jurnal Pendidikan Agama Islam, 2021)
Abstract The phenomenon of online learning has resulted in problems for the environment for administering Madrasah diniyah education by pursuing various innovations to create and implement quality Al-Qur'an reading and writing learning as a form of the existence of institutions in the Covid-19 era. This research was designed with a descriptive qualitative method. Data collection is done by collecting books or references that are relevant and accurate, as well as reading and studying to obtain data or conclusions related to the discussion. While the validity of this research data using observation and document analysis. The results of this study include several innovations that teachers can create and implement during the online learning concept: Learning from Home: Collaboration between Schools and Parents, Online Learning as an Opportunity as well as a Challenge and Blended Learning Learning Models in the Covid-19 Pandemic. Keywords: Innovation, Learning, Coronavirus Desease (COVID-19)